2021
DOI: 10.1021/acs.jpcb.1c01243
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Nonlinear Optical and Structure–Property Relationship Studies of Pyridine-Based Anthracene Chalcones Using Z-Scan, Degenerate Four-Wave Mixing, and Computational Approaches

Abstract: The structural, thermal, linear, and femtosecond third-order nonlinear optical (NLO) properties of two pyridine-based anthracene chalcones, (2E)-1-(anthracen-9-yl)-3-(pyridin-2-yl)­prop-2-en-1-one (2PANC) and (2E)-1-(anthracen-9-yl)-3-(pyridin-3-yl)­prop-2-en-1-one (3PANC), were investigated. These two chalcones were synthesized following the Claisen–Schmidt condensation method. Optically transparent single crystals were achieved using a slow evaporation solution growth technique. The presence of functional gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…In 1960, Mainman's discovery of laser technology laid the foundation for studying nonlinear optics (NLOs), which involve the interaction of high-intensity laser light with matter. 1 Over time, various methods such as Z-scan, 2,3 four-wave mixing (FWM), 4,5 third harmonic generation (THG), 6 second harmonic generation (SHG), 7 and spatial self-phase modulation (SSPM) 8,9 have been developed to analyze nonlinear optical parameters. Among these methods, SSPM has gained significant attention in recent years due to its relatively simple experimental setup and short measurement time as compared to others.…”
Section: Introductionmentioning
confidence: 99%
“…In 1960, Mainman's discovery of laser technology laid the foundation for studying nonlinear optics (NLOs), which involve the interaction of high-intensity laser light with matter. 1 Over time, various methods such as Z-scan, 2,3 four-wave mixing (FWM), 4,5 third harmonic generation (THG), 6 second harmonic generation (SHG), 7 and spatial self-phase modulation (SSPM) 8,9 have been developed to analyze nonlinear optical parameters. Among these methods, SSPM has gained significant attention in recent years due to its relatively simple experimental setup and short measurement time as compared to others.…”
Section: Introductionmentioning
confidence: 99%
“…The results of crystallization can vary depending on the rate of evaporation, with differences observed between slow and rapid evaporation methods, such as oven drying and spray drying. Maidur et al have documented the successful preparation of optically transparent single crystals of two pyridine-based anthracene chalcones using the slow evaporation solution growth technique [3]. Similarly, Hetmanczyk et al have reported the formation of two polymorphic forms of hydroxy acetophenone through slow and fast evaporation of polar and non-polar solutions, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dextran is an α-glucan variant characterized by a continuous main chain of α- (1,6) glycosidic bonds and branch linkage through α-(1,2), α- (1,3), and α- (1,4) glycosidic bonds [5]. The high proportion of α- (1,6) bonds in dextran confers high solubility in water, whereas an increased proportion of α-(1,3) bonds reduces solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Several chalcone derivatives have been investigated theoretically and experimentally for their NLO properties. [6][7][8][9][10][11][12] Besides the electron-donating/withdrawing strength of substitutional group(s), molecular aggregation was reported to enhance the NLO property of their individual molecules. [13][14][15][16][17][18] The molecular aggregation interplayed via the intermolecular interactions, i.e., dipole-dipole interaction, p-p stacking, hydrogen bonding, or halogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Several chalcone derivatives have been investigated theoretically and experimentally for their NLO properties. 6–12…”
Section: Introductionmentioning
confidence: 99%